The Effect of Fermentation and Storage Temperature on the Viability of Lactiplantibacillus plantarum subps. plantarum Dad-13 on Yogurt-Like Drink - Aristya, Aristya; Utami, Tyas; Suroto, Dian Anggraini; Rahayu, Endang Sutriswati (Indonesian Food and Nutrition Progress, 2024)
This study aims to assess the viability of the cell population during the fermentation process and storage at various temperatures. Probiotic bacteria, Lactiplantibacillus plantarum subsp. plantarum Dad-13, procured from the Center for Food and Nutrition Studies UGM, was utilized as a starter in manufacturing a yogurt-like drink. During the manufacture of the yogurt-like drink, cell counts were evaluated prior to and following a 12-hour fermentation period at temperatures of 30 ℃, 37 ℃, and 42 °C. The samples that have the highest viability cell (30 °C) were selected for further study and stored for 25 days at 26 °C, and for 50 days at 10 °C and 4 °C. The cell count was assessed every 5 days using MRS Media.The result indicates that fermenting at 42 °C led to a notably lower cell growth rate of 0.2 log cycles compared to fermenting at 30 °C and 37 °C, leading to cell growth of 1.37 and 1.31 log cycles, respectively. The viability of Lactiplantibacillus plantarum subsp. plantarum Dad-13 in a yogurt-like drink was not significantly different after being stored for 50 days at temperatures of 10 °C and 4 °C. The decline in cell counts of Lactiplantibacillus plantarum subsp. plantarum Dad-13 in samples stored at 10 °C and 4 °C was 0.65 and 0.34 log cycles, respectively. Conversely, at 26 °C, the viability decreased significantly, resulting in a reduction in number of 2.05 log cycles.